Influence of the microstructure on the resulting 18R martensitic transformation of polycrystalline Cu?Al?Zn thin films obtained by sputtering and reactive annealing - Domenichini, Pablo Exequiel; Condo, Adriana Maria; Soldera, F.; Sirena, Martin; Haberkorn, Nestor Fabian (Elsevier Science Inc, 2016)
Fil: Domenichini, Pablo Exequiel. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina